Theory of Quantum Information with Memory - Chang, Mou-Hsiung (Berlin ; Boston : De Gruyter, 2022)
This book provides an up-to-date account of current research in quantum information theory, at the intersection of theoretical computer science, quantum physics, and mathematics. The book confronts many unprecedented theoretical challenges generated by infi nite dimensionality and memory effects in quantum communication. The book will also equip readers with all the required mathematical tools to understand these essential questions.
Frontmatter -- Preface -- Introduction -- Contents -- 1 Basic notation and preliminaries -- 2 Formulation of quantum systems -- t
Issued also in print.
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 02. Mai 2023)
Keywords: Electronic books; Information theory; Memory management (Computer science); Memory management (Computer science).; Quantum communication; Channel Capacities; Memory Quantum Channels; Quantum Entanglement; Quantum Entropy; Quantum States; COMPUTERS / Information Theory; Channel Capacities; Memory Quantum Channels; Quantum Entanglement; Quantum Entropies; Quantum States